The Contribution of Studentsâ Self-Efficacy and Anxiety toward Studentsâ Speaking Achievement of Eighth Grade Students at SMP N 1 Denpasar in Academic Year 2015/2016 - ., Ida Ayu Ratsitha Dewi; ., Prof. Dr. Anak Agung Istri Ngr. Marha; ., Dewa Ayu Eka Agustini, S.Pd., M.S. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
This research aims at investigating (1) the contribution of studentsâ self-efficacy toward studentsâ speaking achievement, (2) the contribution of studentsâ anxiety toward studentsâ speaking achievement, and (3) the contribution of studentsâ self-efficacy and anxiety toward studentsâ speaking achievement at eighth grade students in SMP N 1 Denpasar. This research used ex-post facto research design. The population of this research was the eighth grade students of SMP N 1 Denpasar. 75 students were selected as sample of this research by using simple random sampling technique. The data were collected by employing Self-Efficacy Questionnaire, Foreign Language Classroom Anxiety Scale, and Speaking Documentation. The data showed that the studentsâ self-efficacy, anxiety, and speaking achievement are categorized in the moderate level. The collected data were analyzed by using simple and multiple regression. The result of analysis showed that: (1) there is contribution of studentsâ self-efficacy toward studentsâ speaking achievement at 53.1%, (2) there is contribution of studentsâ anxiety toward studentsâ speaking achievement at 9.8%, and (3) there is contribution of studentsâ self-efficacy and anxiety toward studentsâ speaking achievement at 56.2%. In detail, the effective contribution of self-efficacy is 50.27% and effective contribution anxiety is 5.92% toward studentsâ speaking achievement.keyword : Anxiety, Self-Efficacy, and Speaking Achievement